Causal relationship among obesity and body fat distribution and epilepsy subtypes - Zhou, Kaiping; Yang, Huan; Chen, Ruomeng; Wang, Weiping; Qu, Zhenzhen (Frontiers in Neurology, 2022)
Objective: The observational studies indicate an association between obesity and epilepsy, but it is unclear whether such an association responds to causality. The objective of this study was to determine the causal relationship between obesity and fat distribution and epilepsy subtypes based on waist circumference, hip circumference (HP), waist-hip ratio (WHR), and body mass index (BMI). Methods: A two-sample Mendelian randomization study was conducted separately for the four indicators of obesity and epilepsy and its nine subtypes, with reverse Mendelian randomization and multivariate Mendelian randomization for significant outcomes. Results: A two-sample Mendelian randomized analysis informed us that waist circumference was a risk factor for juvenile myoclonic epilepsy (beta = 0.0299, P = 4.60 × 10–3). The increase in hip circumference increased the risk of juvenile myoclonic epilepsy and epilepsy (all documented cases), with effect values of 0.0283 (P = 2.01 × 10–3) and 0.0928 (P = 1.40 × 10–2), respectively. Furthermore, children with a higher BMI exhibit a higher risk of epilepsy (beta = 0.0148 P = 1.05 × 10–3). The reverse Mendelian randomization study revealed that childhood absence epilepsy increased its BMI (beta = 0.8980, P = 7.52 × 10–7), and adolescent myoclonic epilepsy increased its waist circumference (beta = 0.7322, P = 3.26 × 10–2). Multivariate Mendelian randomization revealed that an increase in hip circumference and waist-hip ratio increased the risk of myoclonic epilepsy in adolescents, with an effect value of 0.1051 (P = 9.75 × 10–4) and 0.1430 (P = 3.99 × 10–3), respectively, while an increase in BMI and waist circumference instead decreased their risk, with effect values of –0.0951 (P = 3.14 × 10–2) and-0.0541 (P = 1.71 × 10–2). In contrast, multivariate Mendelian randomization for childhood absence epilepsy and epilepsy (all documented cases) did not identify any independent risk factors.